Perioperative Pediatric Transfusion Strategy - Ahmad Nur Islam; Elizeus Hanindito; Muhammad Ramli Ahmad; Maman Surya Permana; Hanna Aulia Namirah (Nusantara Medical Science Journal, 2024)
Introduction: In the modern healthcare system, blood transfusion is an essential treatment that plays a significant role in the clinical improvement of adult and pediatric patients. Given the physiological and hematological differences between children and adults, careful planning and an individualized approach are essential to maximize its effectiveness and avoid serious side effects. Method:  A thorough review of the literature was performed, utilizing PubMed, Embase, and the Cochrane Library, to gather evidence on pediatric perioperative transfusion practices. The search encompassed studies published between 2013 and 2024, employing a combination of terms and free-text keywords, as well as Boolean operators, to refine the results. Conclusion: Intraoperative blood loss in pediatric patients requires special attention with an approach that includes pre to postoperative management. This approach must be adapted to the anatomical and physiological differences of children compared to adults. Research, development of universal transfusion strategies, and education and training for medical personnel are essential to improve blood management and prevention of complications.